100 Americans making constitutional history a biographical history - Urofsky, Melvin I. (CQ Press, 2004)
Helps students understand the human side of the Supreme Court's decisions from the early republic to the present. Each biographical profile includes a discussion about the Court decision and how the specific legal issues evolved into great constitutional questions and drama.